Makna Simbolik Budaya Marhabaan bagi Kalangan Nahdlatul Ulama - Setiawan, Wawan (Program Studi Studi Agama-Agama Pascasarjana UIN Sunan Gunung Djati Bandung, 2020)
This paper describes the relationship between Islam and local culture. The purpose of this study was to identify and analyze the process and symbolic meaning of the marhabaan culture among Nahdlatul Ulama, precisely at Al-Quwwah Islamic Boarding School, Bandung City. The method used in this research is qualitative, which clearly defines various kinds of research procedures, so that it will produce descriptive data from what is observed in marhabaan cultural activities, both written and oral. This method aims to know and understand a phenomenon experienced by research subjects such as motives, behavior, opinions, interactions, language, actions, motivation and so on naturally by using various natural methods. The results of this study explain the marhabaan process from beginning to end, then explain the shaving of baby's hair, the symbolic meaning of banana, the symbolic meaning of menyan, the symbolic meaning of ulen (glutinous rice), the symbolic meaning of traditional cakes, and the symbolic meaning of water. All of this emphasizes that there is a traditional combination from the community between Islamic teachings and local culture.